MODEL BRAIN BASED LEARNING (BBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR PADA POKOK BAHASAN SISTEM INDRA - Liah Badriah; Dani Ramdani (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2018)
The Brain Based Learning (BBL) Model in this reseach is applied for improvement of learning outcomes in primary school for subject of sensory Systems. Metodology of this reseach is true experimental by using control group pretest-posttest design. The population of students class IV SD Negeri Tejamaya. The sample of 2 classes taken total sampling, that one class as experimental class is IV A the number of sample is 35 tudents and the class as control class is IV B the number of sample is 36 students. Data collection techniques are paper test (pretest and posttest) to obtain data on student learning outcomes. The research’s data are done with consider their normality an homogenity, and then the data analysis technique is used mean difference test with t-test with a significant level (?) = 5%. Based on data analysis and hypothesis testing shows that there is a significant increase in learning outcomes of primary school student whose learning process uses the Brain Based Learning (BBL) model. The n-gain value for the experimental class is 0,82 and for the control class 0,62.